Development 3D Virtual Laboratory the Hertz Experiment on the Topic of Sound and Light Waves - Rahmansyah Rahmansyah; Khaeruddin Khaeruddin; Usman Usman (Department of Physics Education, Universitas Mataram, 2026)
This study is development research aimed at determining the validity, practicality, and effectiveness of 3D virtual laboratory media for the Hertz experiment on sound and light wave material. The research sample consisted of 30 eleventh-grade students from the Digital Class of MAN 2 Bone. The method used was Research and Development (R&D) following the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The results showed that the media was declared highly valid by physics learning media experts based on the Gregory test. The media's practicality received ratings of 97.35% from the physics teachers and 82.08% from students, both classified as very practical, indicating its high efficiency in the classroom. Furthermore, the N-gain test on students' interest in physics yielded an average score of 0.49. This indicates a moderate yet positive enhancement in students' learning engagement. Therefore, this 3D virtual laboratory is proven to be a highly practical, valid, and engaging instructional medium that successfully supports the visualization of abstract physics concepts.